A coaxially structured trilayered gallic acid-based antioxidant vascular graft for treating coronary artery disease. (15th January 2021) - Das, Ankita; Ahmad Shiekh, Parvaiz; Kumar, Ashok
Graphical abstract: Abstract: Atherosclerosis is the most common type of cardiovascular disease that involves blockage of the coronary arteries of the heart. The current surgical procedure followed in clinical settings to treat abnormal narrowing of blood vessels is the percutaneous coronary intervention. This technique involves a mesh-like, tubular construct called a stent, which is surgically placed inside arteries to treat narrowed vessels and avoid blockage. However, most of the implants suffer from restenosis problem, due to proliferation and migration of vascular smooth muscle cells (SMCs) within the stents. In this work, a biomimetically designed trilayered electrospun conduit of poly-glycolic acid and polycaprolactone blend was sandwiched between gallic acid-containing antioxidant oxygen-releasing polyurethane to serve as a potential stent to avoid restenosis. The selectivity of gallic acid towards inhibiting the growth of SMCs will enable rapid re-endothelialization of the damaged blood vessels. The scaffolds were fabricated by electrospinning of the polymers on a 2 mm diameter rotating collector to mimic the vessel diameter of the coronary arteries. Characterization of the scaffolds has been carried out using fourier transform infrared spectroscopy, electron microscopy, thermal analysis, antioxidant potential assay, and haemocompatibility. The tubular constructs had a strut thickness of ~ 275 µm and could scavenge 92% of the free radicals in just 15 min. The fabricated material was also able to attenuate induced oxidative stress on cells and maintained 68% cell viability. More importantly, the presence of gallic acid was able to reduce the growth of smooth muscle cells by 40% on the scaffolds, making it a feasible material for stent fabrication. The fabricated polymer-based material will be a potent cardiovascular implant for treating blocked arteries.